2021
DOI: 10.32674/jis.v11i4.2427
|View full text |Cite
|
Sign up to set email alerts
|

International Student Migration in Finland

Abstract: There is increasing attention on the retention of international students with many stakeholders desiring to keep international students for long-term economic growth. This study examines the factors affecting international students to stay in Finland five years after initial enrolment with particular focus on the role graduation plays in students staying or leaving. Tracking 11 (years) entering cohorts for five years across national (Finland) data registries, we found evidence of an inverse relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…European students are often more open to migration due to programmes like Erasmus that encourage mobility (Mendoza et al, 2019). Having a stable, professional job is crucial to students' decision to stay, but limited networking opportunities in the job market can make it difficult to find work, leading them to return home (Mathies and Karhunen, 2021). Inability to create social capital can be another reason why students choose not to stay in the host country (Wang and O'Connell, 2020).…”
Section: Return To Home Countrymentioning
confidence: 99%
“…European students are often more open to migration due to programmes like Erasmus that encourage mobility (Mendoza et al, 2019). Having a stable, professional job is crucial to students' decision to stay, but limited networking opportunities in the job market can make it difficult to find work, leading them to return home (Mathies and Karhunen, 2021). Inability to create social capital can be another reason why students choose not to stay in the host country (Wang and O'Connell, 2020).…”
Section: Return To Home Countrymentioning
confidence: 99%
“…Students seek out these opportunities from gaining a competitive edge in the labor market (King & Raghuram, 2013) to experiencing an overseas adventure in a manner that is acceptable to their families and society (King & Sondhi, 2018). On the other side, institutions and governments have long viewed international students as a way to generate revenue and fill shortages in their labor markets (Cantwell, 2015;Mathies & Weimer, 2018;Riaño, Van Mol, Raghuram, 2018); many are increasingly interested in understanding the reasons international students stay or leave the host country after graduation (Mathies & Karhunen, 2021a, 2021b. Higher education operates as a 'quasi-market' with the international student mobility as one of the many submarkets within it (Kauppinen, Mathies, & Weimer, 2014;Teixeira, Jongbloed, Dill, & Amaral 2004).…”
Section: Reflections On Leavingmentioning
confidence: 99%
“…They also have a more global outlook when compared with local students. Scholars have therefore suggested that international students should receive help to integrate into their host destinations [ 9 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Final year students generally care both about their academic results (which are relevant for further studies) and their local network (which relates to their intention to stay) [ 19 ]. Scholars focused on year of graduation as a moderating factor [ 9 ]. There is a research gap on the role of education level.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation